Complications of mediastinal neural tumours. Issue 4 (July 1971) - Parish, Christopher
Abstract : Thirty-two mediastinal neural tumours were seen in the East Anglian Regional Thoracic Surgical Unit at Cambridge between October 1952 and July 1970. The descending order of frequency was neurofibroma, ganglioneuroma, neurilemmoma, neurofibrosarcoma, and neuroblastoma. The literature relating to these tumours is reviewed and the pathological and clinical complications encountered in this series and in the literature are described.